MEASURING INSTABILITY OF FOREIGN DIRECT INVESTMENT FLOWS IN LATVIA - Limanskis, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Fluctuations of Foreign Direct Investment (FDI) flows constitute an acute research problem globally and in Latvia studies. Already before COVID19, negative flows occurred. The research aim is to investigate stability in FDI in Latvia applying theory of dynamical system to big database of 129 countries of origin of FDI covering the whole period of regained statehood. The primary methods used are standard deviation and correlation. The main research result is disclosing growing instability of FDI flows in Latvia despite joining the EU and Eurozone. Novelty consists of research methodology justification, plotting analytical table, calculation of sigma and correlations for FDI flows for the periods before and after Latvia joined the EU, and drawing conclusions.